O artista no instagram: modos de uso, processos e arquivos de criação - Lima, Júlia Meireles de (2022)
This research analyzes the creative process in the midst of the communicative dynamics that exist in digital media. To this end, the study was based on the social network Instagram (2010) and its tools, as they foster new perspectives in the creative, visual and social scope of artist users. The notion of the creative process, as developed by Cecilia Almeida Salles, is the starting point for the analysis of creative practices which are, in part, enhanced by the use of social networks such as Instagram - and which appear throughout the entire research. Aiming at contextualizing the chosen platform, the research is based on the studies of Lev Manovich and Sarah Frier in order to analyze Instagram under the aspect of its marketing and aesthetic evolution; taking into account issues inherent to its use, such as image and photographic production, daily exposure, interactivity and the algorithm, through the work of theorists such as Paula Sibilia and Eli Pariser. From this analysis, we seek to understand how the production dynamics raised by Instagram can both bring clues and changes to the creative process of artists, and can serve as a direct support for their work. To this end, we investigate the artists Samuel de Saboia and Isabella Galvão, who use the platform as part of their daily lives and also as a medium for the dissemination of their works and processes; and artist Gustavo von Ha who, unlike the others, uses the platform as a direct support for his artistic production. Starting from an analysis that sometimes goes deeper into the unique issues of an individual artist, and at times establishes dialogues with others present on the platform, the research approaches the work of theorists such as Nicolas Bourriaud, Gilles Lipovetsky and Hito Steyerl; makes observations about the use of the platform; and, also counting on interviews carried out with some of the aforementioned artists, it presents a possible path of creative processes that are sometimes exposed, sometimes mediated by the social network